Encyclopedia of Polymer Science and Technology 2014
DOI: 10.1002/0471440264.pst626
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐oxazoline)s

Abstract: Research in the field of poly(2‐oxazoline)s (PAOx) is rapidly expanding as this polymer class combines high synthetic versatility and biocompatibility, opening up the way to highly functional (biocompatible) materials. PAOx are prepared by living cationic ring‐opening polymerization (CROP) of 2‐oxazolines. The variety of 2‐oxazoline monomers that are readily available or can easily be synthesized allows for tuning of polymer properties and introduction of diverse functionalities. Moreover, thanks to the living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 321 publications
1
11
0
Order By: Relevance
“…α‐deprotonation of 2‐methyl‐2‐oxazoline followed by alkylation towards more complex 2‐oxazolines, are also reported . For a more detailed overview and description of the synthesis of 2‐oxazolines see the recent review by Verbraeken et al …”
Section: Synthesis Of 2‐oxazoline Monomersmentioning
confidence: 99%
“…α‐deprotonation of 2‐methyl‐2‐oxazoline followed by alkylation towards more complex 2‐oxazolines, are also reported . For a more detailed overview and description of the synthesis of 2‐oxazolines see the recent review by Verbraeken et al …”
Section: Synthesis Of 2‐oxazoline Monomersmentioning
confidence: 99%
“…Subsequently, we attempted the α-deprotonation of 2-methyl-2-oxazoline (MeOx) followed by a substitution reaction with an alkyl bromide/iodide. , More specifically, MeOx was deprotonated using n -butyllithium/tetramethyl­ethylenediamine, and the obtained carbanion was then reacted with 1 H ,1 H ,2 H ,2 H -perfluorooctyl bromide to form 2-(1 H ,1 H ,2 H ,2 H ,3 H ,3 H -perfluorononyl)-2-oxazoline (Scheme ). Unfortunately, the attempt to apply this procedure for the synthesis of fluorinated 2-oxazolines failed, and the usage of perfluorooctyl iodide was unsuccessful, too.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we first attempted to form the 1H,1H,2H,2H-perfluorooctylcyanide by reaction of the 1H,1H,2H,2H-perfluorooctyliodide with sodium cyanide, in analogy to the report of Subsequently, we attempted the α-deprotonation of 2-methyl-2-oxazoline (MeOx) followed by a substitution reaction with an alkylbromide/iodide. 39,40 More specifically, MeOx was deprotonated using n-butyllithium/tetramethylethylenediamine 41 Alternatively, the failure may be (partially) due to elimination of HBr from the fluorinated reactant in presence of a strong base. Thus, it could be concluded that this method is not applicable for functionalization of 2-oxazolines by fluorine containing alkyl bromides/iodides.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…1,4−6 PAOx are prepared by living cationic ring-opening polymerization (CROP) of 2-oxazolines, and their polymerization mechanism has been studied widely (Scheme 1). 7 One of the main advantages of the CROP is that its living nature provides good control over the molar mass distribution, that is, narrow dispersity (Đ), and very high endgroup fidelity. 8,9 Additionally, a broad range of structures and polymer properties are easily accessible by variation of the monomer structures.…”
mentioning
confidence: 99%
“…During the past decades, researchers have been searching for alternative biocompatible polymers, that “outperform” the gold standard in the field, poly­(ethylene glycol). In this respect, poly­(2-alkyl/aryl-2-oxazoline)­s (PAOx), more specifically, poly­(2-methyl-2-oxazoline) (PMeOx) and poly­(2-ethyl-2-oxazoline) (PEtOx), have been widely investigated for their use in biomedical applications. , PAOx are prepared by living cationic ring-opening polymerization (CROP) of 2-oxazolines, and their polymerization mechanism has been studied widely (Scheme ). One of the main advantages of the CROP is that its living nature provides good control over the molar mass distribution, that is, narrow dispersity ( Đ ), and very high end-group fidelity. , Additionally, a broad range of structures and polymer properties are easily accessible by variation of the monomer structures. The CROP of 2-oxazolines consists of three steps, namely, the initiation, propagation, and termination.…”
mentioning
confidence: 99%